Biological evaluation of folic acid functionalized nano‐zeolitic imidazolate framework‐8 for cancer therapy - Lai, Xie Yong; Muhamad Ibrahim, Abdul Malek; Azren Aida, Asmawi; Rosniza, Razali; Afiq, Azil; Nur Aininie, Yusoh; Nurul Akmarina, Mohd Abdul Kamal (Springer Berlin Heidelberg, 2024)
Conventional chemotherapy often results in toxicity to normal cells and hampers cancer treatment efficacy. Cancer targeting via surface-functionalized nanocarrier offers an excellent opportunity for tackling this unwanted issue. However, a comprehensive understanding of its toxicity and safety in biological entities remains limited. In this study, we report the cancer-selectivity of surface-functionalized nano-zeolitic imidazolate framework-8 (FA@nZIF-8) and its safety characteristics in small organisms including zebrafish embryos and brine shrimp. The FA@nZIF-8 exhibited higher selectivity (3.95) towards cancer cells (MCF7) compared to pure nZIF-8. Moreover, this functionalized nano-ZIF-8 not only enhanced permeability performance but also appeared to be a significant survivability advantage, 80% (P < 0.001) with a higher survival rate compared with pure nZIF-8 at the 96-h mark. No scoliosis appeared in healthy zebrafish embryos for both nanoparticle systems. Monitoring brine shrimps showed minimal toxicity induction at a certain level of concentration. This study suggests that surface-functionalized FA@nZIF-8, with its cancer-selective behavior and promising safety characteristics, has bright potential for further exploration in cancer therapy.